Co-expression of multi-genes for polynary perovskite electrocatalysts for reversible solid oxide cells - Xiaoxin Zhang; Hongyuan He; Yu Chen; Guangming Yang; Xiao Xiao; Haiping Lv; Yongkang Xiang; Shuxiong Wang; Chang Jiang; Jianhui Li; Zhou Chen; Subiao Liu; et al. (Nature Communications)
Abstract High-entropy LnBaCo2O5+δ perovskites are explored as rSOC air electrodes, though high configuration entropy (S config) alone poorly correlates with performance due to multifactorial interactions. We systematically engineer LnBaCo2O5+δ perovskites (Ln = lanthanides) with tunable S config and 20 consistent parameters, employing Bayesian-optimized symbolic regression to decode activity descriptors. The model identifies synergistic contributions from S config, ionic radius, and electronegativity, enabling screening of 177,100 compositions. Three validated oxides exhibit superior activity/durability, particularly (Pr0.05La0.4Nd0.2Sm0.1Y0.25)BaCo2O5+δ , showing enhanced oxygen vacancy concentration and disordered transport pathways. First-principles studies reveal optimized charge transfer kinetics via cobalt-oxygen bond modulation. Further, the interplay between first ionization energy, atomic mass, and ionic Lewis acidity dictates stability. This data-driven approach establishes a quantitative framework bridging entropy engineering and catalytic functionality in complex oxides.